2015
DOI: 10.1111/pbi.12505
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the production of cell wall‐deconstructing enzymes in lignocellulosic biomass and their utilization for biofuel production

Abstract: SummaryMicrobial cell wall‐deconstructing enzymes are widely used in the food, wine, pulp and paper, textile, and detergent industries and will be heavily utilized by cellulosic biorefineries in the production of fuels and chemicals. Due to their ability to use freely available solar energy, genetically engineered bioenergy crops provide an attractive alternative to microbial bioreactors for the production of cell wall‐deconstructing enzymes. This review article summarizes the efforts made within the last deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 137 publications
(228 reference statements)
0
22
0
Order By: Relevance
“…One of the most interesting groups in the present study includes genes whose expression is only detected in one tissue. This kind of genes and their promoters are of particular interest because they can be used as expression markers and to drive tissue‐specific expression in transformed organisms as illustrated by the production of cell wall‐deconstructing enzymes in planta (Park et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…One of the most interesting groups in the present study includes genes whose expression is only detected in one tissue. This kind of genes and their promoters are of particular interest because they can be used as expression markers and to drive tissue‐specific expression in transformed organisms as illustrated by the production of cell wall‐deconstructing enzymes in planta (Park et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The use of different promoters in recombinant protein expression systems, in general, has been reviewed extensively [96][97][98][99]. The promoters used in heterologous expression systems vary significantly in their nature, activity, location, and mode of action.…”
Section: Promoters Signal Peptides and Targeted Expressionmentioning
confidence: 99%
“…The promoters used in heterologous expression systems vary significantly in their nature, activity, location, and mode of action. Studies revealed that in plants, the signal peptides and promoters are available to express, guide and store the protein in almost all cellular and extracellular targets [99]. Among the different types of promoters, the constitutive [ One of the major disadvantages, when plants are used as an expression platform, is the plant-specific secondary modifications added on to the proteins, which may make them immunogenic and hence useless in many applications.…”
Section: Promoters Signal Peptides and Targeted Expressionmentioning
confidence: 99%
“…Importantly, we include only enzymes that are active in planta concurrent with cell wall development. The engineering of plants to accumulate hyperthermophilic or inactive cell wall-degrading enzymes has been well reviewed in other works (Mir et al, 2014;Damm et al, 2016;Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%